2018
DOI: 10.5539/jas.v10n12p249
|View full text |Cite
|
Sign up to set email alerts
|

Forage Yield and Silage Quality of Intercropped Maize+Soybean With Different Relative Maturity Cycle

Abstract: The success of maize+soybean intercrop depends on the correct synchronism between species phenological stages at the silage point. Due to it, the experiment was carried out to evaluate maize+soybean intercrop forage yield and silage quality using crops with different maturity cycle combination. The experiment used a randomized complete block design with a 2 × 3 factorial scheme. Treatments consisted of two maize hybrids (1: P1630YHR-early cycle and 2: middle cycle P30F53VYHR) and two soybean cultivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
(34 reference statements)
2
2
0
1
Order By: Relevance
“…According to Neves & Gai (2017), the pH values found in the present experiment characterize good quality silage and are similar to those observed in other studies using sole maize crop silage (Neves & Gai, 2017;Pauli et al, 2017 ) and composed silage (corn + soybean) (Stella et al, 2016;Batista et al, 2018;Batista et al, 2019). In this context, it can infer that the addition of soybean biomass does not affect the microbial fermentation of the ensiled biomass.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…According to Neves & Gai (2017), the pH values found in the present experiment characterize good quality silage and are similar to those observed in other studies using sole maize crop silage (Neves & Gai, 2017;Pauli et al, 2017 ) and composed silage (corn + soybean) (Stella et al, 2016;Batista et al, 2018;Batista et al, 2019). In this context, it can infer that the addition of soybean biomass does not affect the microbial fermentation of the ensiled biomass.…”
Section: Resultssupporting
confidence: 91%
“…These results corroborate with other studies that evaluated these intercrop (Batista et al, 2018;Batista et al, 2019) with different proportions of ensiled biomass (Stella et al, 2016). According to Stella et al (2016), from the standpoint of chemical composition, the ensiled corn biomass could be composed of up to 50% soybean plant, resulting in improved silage traits (CP) without affecting its fermentation quality (pH and N-NH3 concentration).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Segundo os autores, ambas as espécies possuem características complementares: o milho por ser uma cultura C 4 exigente em nitrogênio e possuir porte relativamente mais alto, e a soja de metabolismo C 3 , fixadora de nitrogênio, que ocupa um nicho ecológico relativamente baixo; permitem que ambas as culturas coexistam de forma equilibrada. Portanto, o consórcio milho-soja pode ser implementado em qualquer área, onde o milho e soja são cultivadas, sem que ocorra perdas na cultura do milho consorciado quando comparado ao monocultivo (Saleem et al, 2011;Ijoyaha e Fanenb, 2012;Zerihun et al, 2013;Du et al, 2017;Batista et al, 2018;Batista et al, 2019). O índice de equivalência de área (IEA) é considerado eficiente quando for superior a 1,0 (Vandermeer, 1990) e tanto os consórcios estabelecidos com o milho em fileiras simples quanto em duplas foram eficientes (Tabela 7).…”
Section: Resultados E Discussão Ensaio 1: Consórcio De Fileiras Simplunclassified
“…In their study of intercropping soybean and maize using variable patterns, the authors in [17] concluded that intercropping stimulated the growth of maize, which was negatively reflected on the growth of the accompanying soybean. In a similar soybean-maize intercropping system, the authors in [32] reported that fodder maize will be ready for harvesting and ensiling, while soybean is in the R7 developmental stage.…”
Section: Discussionmentioning
confidence: 99%